Computer methods in electrical power distribution for petronas gas industrial plant - Norahida, Ibrahim (2008)
Power system analysis software used to determine the amount use of power of the electrical power network for utility, industrial, and commercial industries. Along with all of the recent technological advances, there have been similar advances in power system analysis software. Engineers use this software to design, operate and control power systems. Such software allows engineers to solve power system analysis problems more easily. This analysis is intended as introductory information for Petronas Gas plant engineering wanting to acquire power system analysis software. Additionally, this analysis addresses how such software can be applied in the Petronas Gas industrial plant. This analysis is more focuses on the power flow analysis. A power flow will calculates the voltage drop on each feeder, the voltage at each bus, and the power flow in all branch and feeder circuits. It is worked by using the software of SKM Power Tools for Windows.